Korelasi Komponen Pertumbuhan dan Hasil pada Pertanian Terpadu Padi-Azolla - Etty Safriyani; Mery Hasmeda; Munandar Munandar; Firdaus Sulaiman (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Safriyaniet al, 2018. Correlation of Growth and Product Components on Integrated farming Padi-Azolla. JLSO 7(1):59-65.In order to increase the growth and production of rice plants that support sustainable agriculture can be done with the azolla application. This study aimed to evaluate the correlation of the components of growth and yield on rice-azolla production. The research was conducted on Karang Ketuan Subdistrict South Lubuklinggau II Subdistrict Lubuklinggau City from January to April 2018. This study used a randomized block consisting of K1=250 kg urea ha-1 without azolla, K2=250 kg urea ha-1+azolla 1000 kg ha-1, K3=187.5 kg urea ha-1+azolla 1000 kg ha-1, K4=125 kg urea ha-1+azolla 1000 kg ha-1, K5=62.5 kg urea ha-1+azolla1000 kg ha-1, K6=without Urea+azolla1000 kg ha-1. Data analysis used correlation and path analysis. The results showed that plant height and number of pithy grains correlated on grain weight with higher values than other growth components. Dry weight of straw and harvest index had a direct and positive effect on grain weight with cross coefficients value namely 1.086 and 0.755 representatives. Plant height and number of pithy grains could be used as an indicator of crop production.